DESKRIPSI TEKNIS PENGENDALI TINGGI MUKA CAIRAN INDUSTRI METODE FLOATLESS OMRON 61F - Tadeus, Dista Yoel; Setiono, Iman (Gema Teknologi, 2019)
Device for controlling liquid/water level using the floatless method uses the character of liquid conductivity as an electric current carrying medium. Excitation voltage is generated by the controller and passed to the electrode through an insulated conductor cable. The electrode is submerged in a tank or liquid storage vessel and directly becomes the lower limit and upper limit of the liquid level. Omron 61F is one of the industry-standard floatless control devices that is simple, compact and relatively inexpensive and easily available on the market. Some applications for controlling liquid levels such as water supply and drainage can be done easily and simple wiring. Omron 61F provides a variety of controller types that are tailored to the application conditions and the type of liquid used, ranging from purified clean water, dirty water, salt water, to several types of acidic liquids.